2015
DOI: 10.1016/j.trre.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of liver transplant injury and regeneration

Abstract: While improved surgical techniques, post-operative care, and immunosuppression regimens have reduced morbidity and mortality associated with orthotopic liver transplantation (OLT), further improvement of outcomes requires personalized treatment and a better understanding of genomic mechanisms involved. Gene expression profiles of ischemia/reperfusion (I/R) injury, regeneration, and rejection, may suggest mechanisms for development of better predictive tools and treatments. The liver is unique in its regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 89 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Downregulated miRNAs involved in apoptosis include miRNA‐200b and miRNA‐183. Upregulated miRNAs involved in liver regeneration include miRNA‐27a, −494, −1224 and ‐149 . These findings indicate an important role for miRNA in the regulation of hepatic IRI.…”
Section: Molecular Mechanisms Of Irimentioning
confidence: 83%
“…Downregulated miRNAs involved in apoptosis include miRNA‐200b and miRNA‐183. Upregulated miRNAs involved in liver regeneration include miRNA‐27a, −494, −1224 and ‐149 . These findings indicate an important role for miRNA in the regulation of hepatic IRI.…”
Section: Molecular Mechanisms Of Irimentioning
confidence: 83%
“…Previous studies have investigated HIRI-induced liver damage with insufficient energy supply, which may be exacerbated by the degradation of mitochondrial autophagy (20). It is well established that mitochondrial autophagy and its derivatives potently and reversibly decrease mitochondrial transmembrane potentials and inhibit cell death in a concentration-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Livers without injury have been demonstrated to exhibit decreased apoptosis compared with their counterparts, following HIRI and a direct effect of apoptosis on tissues is the suppression of energy production by mitochondria (21). At the gene expression level, certain studies (20) have reported that Bcl-2 secured correct rejoining of the DNA broken end to protect DNA integrity as DNA damage response post-HIRI, indicating that Bcl-2-associated regulatory mechanisms serve an important role in HIRI; this may explain why Bcl-2 downregulation results in increased sensitivity to HIRI. These previous studies suggest that the downregulation of anti-apoptotic genes and a subsequent increase in apoptosis may impair cell survival post HIRI (12).…”
Section: Discussionmentioning
confidence: 99%
“…ASC activity also decreases antiapoptotic BCL2 expression while increasing proapoptotic caspase 3 expression . In addition, HIRI also activates expression of HO‐1 (also known as HSP32), which provides protection against HIRI through carbon monoxide (CO) generation . Mechanistically, HO‐1 promotes the expression of several antiapoptotic proteins through CO generation, including BCL2 and HSP70 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF stimulates hepatocyte proliferation through VEGFR‐1–induced HGF up‐regulation . Specifically, VEGF's binding to LSECs triggers the release of pro‐HGF, which is then cleaved to form HGF . HGF then activates the release of TGF‐α and other downstream signals that promote cell‐cycle transition .…”
Section: Discussionmentioning
confidence: 99%